Does smoking affect your skin? - Lipa, Katarzyna; Zając, Natalia; Owczarek, Witold; Ciechanowicz, Piotr; Szymańska, Elżbieta; Walecka, Irena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Smoking has a negative influence on human beings. Carcinogens detected in smoke can increase the risk of developing chronic disorders, cancer and premature death. Nicotine can also affect dermatological diseases such as psoriasis, hidradenitis suppurativa, chronic dermatoses, alopecia, lupus erythematosus, polymorphous light eruption, skin cancer and tobacco-associated oral lesions. Advanced education at a doctor’s surgery in various medical occupations can change the bad habits and protect people from the consequences.